Aortic and Mitral Valve Replacement: three Years of Experience - Fernández Perdomo, Gonzalo; Nozar, José V; Bustin, Jacobo; Estable, Héctor; Lorenzo, Alvaro; Abó, Juan C (Cirugía del Uruguay, 1980)
The experience of the Department of Cardiac Surgery of the Hospital de Clínicas of Montevideo, from jul'y 1976 to september 1979 with 44 aortic and 34 mitral replacements, is reported.